Urgency of Femicide Watch in Implementing SDG 5: Gender Equality to Prevent Femicide in Indonesia - Grace Shella Michelle Ermina Ndun; Rini Fidiyani (Law Research Review Quarterly, 2026)
The persistence of gender-based killings in Indonesia reflects structural challenges in legal recognition, data integration, and institutional coordination in addressing violence against women. Although various laws on the protection of women have been enacted, Indonesian positive law does not explicitly recognise femicide as a gender-based category of homicide, and national data systems do not consistently provide gender-disaggregated monitoring of such cases. This study aims to analyse the urgency of establishing a Femicide Watch mechanism in Indonesia as a strategic instrument to prevent femicide and to examine its relevance within the framework of Sustainable Development Goal (SDG) 5. This research employs a qualitative empirical approach using a socio-legal perspective. Data were collected through in-depth interviews with a legal practitioner and psychologist, as well as officials from a regional women and child protection unit, complemented by secondary data from legislation, judicial developments, institutional reports, and provincial statistics on violence against women. Comparative analysis of international practices was also conducted. The facts show that although a rapid response mechanism for protection services has been established at the national level, the judicial system remains reactive and lacks a comprehensive governance framework to address gender issues. The state's refusal to recognize femicide means that data is not classified, making it difficult to accurately monitor progress. The establishment of mechanisms to systematically monitor killings of women will strengthen legal protections and increase accountability, reaffirming Indonesia's commitment to gender equality and violence reduction in line with the Sustainable Development Goals (SDGs).